Environmental Health Risk Assessment of Consumption of Foodstuffs Containing Organophosphate Residues among Farmers - Imelda Gernauli Purba, Imelda; Kusnoputranto, Haryoto; Wulandari, Ririn Arminsih; Hartono, Budi (Unnes Journal of Public Health, 2025)
The use of pesticides in the agricultural sector results in contamination of foodstuffs by pesticide residues, thus becoming a source of exposure to the body and resulting in health problems. The purpose of this study was to analyse the health risks due to the consumption of foodstuffs containing organophosphate residues in farmers. The design of this study was cross-sectional, employing the Environmental Health Risk Assessment (EHRA). The study population was farmers in the North Dempo District of Pagar Alam. A total of 117 farmers were sampled randomly. Environmental samples consisted of five red chilies and five tomatoes, which were selected purposively. Organophosphate residues were quantified using liquid Chromatography Tandem Mass Spectrometry. Body weight was measured using calibrated body scales. Activity pattern data were collected through interviews using a questionnaire. Data analysis was conducted using the  EHRA formulas. The results demonstrated the presence of Chlorpyriphos in red chillies  at a concentration of 3,05 mg/kg, while Profenofos was found at 0.0731 mg/kg and 0.0118 mg/kg.  The presence of Chlorpyriphos in tomatoes samples at a concentration of 0.4439 mg/kg, while Profenofos was found at 0.0112 mg/kg and 0.2043 mg/kg. The risk quotient  for consumption of red chillies containing Chlorpyriphos was found to be 0.0447, while that for Profenofos was 0.2476. The risk quotient for consumption of tomatoes containing Chlorpyriphos was found to be 0.0302, while that for Profenofos was 2.92. It can be concluded that respondents were at non-carcinogenic health risk due to consumption of tomatoes containing Profenofos.